Blow-Up of Certain Solutions to Nonlinear Wave Equations in the Kirchhoff-Type Equation with Variable Exponents and Positive Initial Energy - Loay Alkhalifa; Hanni Dridi; Khaled Zennir (Journal of Function Spaces)
This paper is concerned with the blow-up of certain solutions with positive initial energy to the following quasilinear wave equation: utt−MNutΔp·u+gut=fu. This work generalizes the blow-up result of solutions with negative initial energy.